Misdiagnosed advanced interstitial pregnancy - A case report (Indian Journal of Case Reports, 2018)
Interstitial pregnancy is a rare and dangerous form of ectopic pregnancy that can be mistaken for a normal intrauterine pregnancy on ultrasonography leading to catastrophic results. Gynecologist should be aware of the potential for mistaking an interstitial pregnancy for intrauterine pregnancy. We present a case of 14 weeks interstitial pregnancy misdiagnosed on abdominal ultrasonography as intrauterine pregnancy with ascites. She was treated as sub-acute intestinal obstruction with severe anemia in pregnancy for 2 days. The correct diagnosis was first made at emergency laparotomy which showed hemoperitoneum and rent involving the right superolateral end of the uterus, with fetus and placenta lying in pouch of Douglas. Wedge resection of the right superolateral end of uterus along with repair done. Lack of suspicion and lack of expertise are a common cause for missing this rare ectopic pregnancy.